Anticancer metallohelices: nanomolar potency and high selectivity. Issue 2 (9th November 2015) - Kaner, Rebecca A.; Allison, Simon J.; Faulkner, Alan D.; Phillips, Roger M.; Roper, David I.; Shepherd, Samantha L.; Simpson, Daniel H.; Waterfield, Nicholas R.; Scott, Peter
Abstract : New optically pure helicate-like architectures are extremely active against cancer cell lines, with IC50 values as low as 40 nM, but nearly three orders of magnitude less active against healthy cells. There is also low toxicity to microbes and amoeba. Abstract : A range of new helicate-like architectures have been prepared via highly diastereoselective self-assembly using readily accessible starting materials. Six pairs of enantiomers [Fe2 L3 ]Cl4 · n H2 O (L = various bidentate ditopic ligands NN–NN) show very good water solubility and stability. Their activity against a range of cancer cell lines in vitro is structure-dependent and gives IC50 values as low as 40 nM. In an isogenic pair of HCT116 colorectal cancer cells, preferential activity was observed against cell lines that lack functional p53. Selectivity is also excellent, and against healthy human retinal pigment epithelial (ARPE19) and lung fibroblast (WI38) cells IC50 values are nearly three orders of magnitude higher. Cisplatin is unselective in the same tests. The compounds also appear to have low general toxicity in a number of models: there is little if any antimicrobial activity against methicillin-resistant Staphylococcus aureus and Escherichia coli ; Acanthamoeba polyphaga is unaffected at 25 μg mL −1 (12.5 μM); Manduca sexta larvae showed clear evidence of systemic distribution of the drug, and rather than any observation of adverse effects they exhibited a significant mean weight gain vs. controls. Investigation of the mode of action revealed no significant interaction of the molecules with DNA, and stimulation of substantial cell death by apoptosis.